MANAJEMEN LABA, TATA KELOLA DAN NILAI PERUSAHAAN - SHEVIN WINARTA; IRENE NATALIA; DEDHY SULISTIAWAN (Jurnal Bisnis dan Akuntansi, 2021)
The purpose of this study is to empirically determine the effect of earnings management and corporate governance practices on firm value. Modified Jones-based discretionary accruals are used as a proxy for earnings management. Firm value is measured by Tobin's Q and corporate governance is evaluated by independent commissioners, managerial ownership, institutional ownership, and auditor reputation. The study uses companies listed in Indonesia Stock Exchange for the 2017-2019 period. The main findings indicate that earnings management has a positive effect on firm value and institutional ownership is able to weaken the effect of earnings management on firm value. This study contributes to market-based accounting research and corporate governance.